Effect of Extraction Methods on Antifungal Activity of Sea Cucumber (Stichopus japonicus) - Amir Husni; Il Shik Shin; Donghwa Chung (agriTECH, 2014)
The objective of this study was to investigate the antifungal activity of the soluble matter (SM) and crude saponins (CS) extracted from Stichopus japonicus using pressurized solvent extraction (PSE) with water or aqueous ethanol as a solvent, in comparison with traditional heat reflux extraction (HRE). The extraction yields were also determined for the SM and CS and compared for each extraction process and solvent. The antifungal activity of the SM and CS, extracted from the body wall of Stichopus japonicus using PSE or HRE with water or 70% aqueous ethanol, were investigated. Both SM and CS exhibited their highest antifungal activity when extracted by HRE with 70% ethanol and by HRE with water, respectively, while their highest yields were obtained when extracted by PSE with water. SM has more antifungal than potassium sorbate but weaker than propyl paraben, while CS has more antifungal than the two antifungal agents.